Recycle energy: waste oil as alternative eco-friendly fuel. Issue 1 (1st December 2022) - Hilda, L; Lubis, R; Misdawati,; Syafiruddin,; Arafah, G R; Halomoan, A Y
Abstract: Used oil is a dangerous and toxic material whose use is strictly prohibited because it damages the environment and human life. Therefore, special handling is needed to dispose of the waste or reuse it with other functions (renewable energy). Researchers are interested in recycling used oil as a fuel that can help overcome the depletion of fossil fuels. This research is an experimental study conducted in a laboratory. Used oil which for a lot of time as waste that is not utilized will affect the environment and also health because it is a pollutant of Hazardous and Toxic Materials (B3). But before being reused, the harmful metals Pb, Fe, Al and Mn are removed by a filtering process, acidification to remove impurities and bind metals that contaminate the oil. After that, it is reused as a very efficient fuel in terms of price compared to using LPG or kerosene.